Digital Marketing: A Service Learning Approach to Revitalizing the Sandal Industry - Dzinnur, Cilda Thesisa Ilmawan; Bangsu, Muhammad; Muzayyin, Achmad (STAI Miftahul ULa Nganjuk, 2024)
This community service project aimed to empower micro, small, and medium enterprises (MSMEs) in Wedoro village, Sidoarjo, by introducing digital marketing strategies to local artisans in the sandal industry. The project utilized the Service Learning (SL) approach, integrating academic learning with community engagement. A series of workshops and mentoring sessions were conducted to train artisans on the use of social media, e-commerce, and online advertising. The project’s outcomes revealed a significant increase in online customer engagement, a 25-40% rise in sales, and an expanded customer base for participants. However, challenges such as content creation and technical skills emerged, highlighting the need for ongoing support and advanced digital marketing training. The findings suggest that digital marketing plays a crucial role in ensuring the resilience and growth of MSMEs, particularly in times of crisis like the COVID-19 pandemic. The project’s success underscores the importance of providing continuous learning opportunities and fostering collaboration between educational institutions, the government, and MSMEs to promote sustainable digital transformation in traditional industries. The implications of this study are significant for future MSME development initiatives, offering a model for integrating digital tools into local businesses to foster long-term economic growth and competitiveness.